2004
DOI: 10.1097/01.smj.0000051150.63130.e8
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Cholecystocutaneous Fistula

Abstract: Spontaneous cholecystocutaneous fistula is rarely observed today because of the early diagnosis and management made possible by ultrasonography, broad-spectrum antibiotics, and effective surgical management of biliary tract disease. We present a case of spontaneous cholecystocutaneous fistula due to cholecystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 7 publications
0
26
0
2
Order By: Relevance
“…However since then less than 20 cases of spontaneous cholecystocutaneous fistula have been reported in last 50 years. [2,4,5] So far no case report of a spontaneous malignant cholecystocutaneous fistula has been published. Gall bladder cancer is an aggressive disease with a dismal prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However since then less than 20 cases of spontaneous cholecystocutaneous fistula have been reported in last 50 years. [2,4,5] So far no case report of a spontaneous malignant cholecystocutaneous fistula has been published. Gall bladder cancer is an aggressive disease with a dismal prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In case of a high clinical suspicion prompt diagnosis tonitis, subacute perforation resulting in an abscess around the gallbladder, or chronic perforation with the formation of an internal or external biliary fistula (2,6). On clinical examination the patient may be febrile and diaphoretic because of the infection but this is not necessarily the case.…”
Section: Spontaneous Cholecystocutaneous Abscessmentioning
confidence: 99%
“…In their review in 1949, Henry and Orr found 36 cases of external biliary fistulas reported after 1890 (1). In the last decades these complications have become very rare, due to the improvements in diagnostic imaging, the use of broad-spectrum antibiotic therapy and advancements in biliary surgery (2,3). We describe here a rare case of spontaneous cholecystocutaneous abscess.…”
mentioning
confidence: 99%
“…Spontaneous cholecystocutaneous fistulae are often the result of neglected biliary tract disease. This is rarely observed today because of the early diagnosis and management made possible by ultrasonography, broad-spectrum antibiotics, and effective surgical management of biliary tract disease 2 . The pathophysiology of this condition has been associated with increased pressure in the gallbladder, secondary to biliary obstruction.…”
Section: Introductionmentioning
confidence: 99%